Creating Value for Clients using a Holistic Approach in Banking Marketing (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This paper investigates how marketing mix strategies' design affects customer value creation. The paper presents the results of empirical research conducted through a questionnaire that aims to show and determine which elements are key in choosing a bank, the extent to which branches and digital services are used, which affects customer satisfaction, loyalty, and customer experience for quality assessment and what are the reasons why clients would leave the current bank and choose a competing bank. The research results indicate that the availability of products and services is important to clients with support that increases the user experience, the application of innovative technologies in creating new offers, and friendly, educated, and friendly staff and channels. Respondents state the reasons for changing the bank: lack of branches, unfriendly or unprofessional staff, unsatisfactory quality of service, excessive fees, and more.